Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.06.30.180737
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of bacterial cell division: Z ring condensation is essential for cytokinesis

Abstract: AbstractHow proteins in the bacterial cell division complex (the divisome) coordinate to divide bacteria remains unknown. To explore how these proteins collectively function, we conducted a complete dynamic characterization of the proteins involved, and then examined the function of FtsZ binding proteins (ZBPs) and their role in cytokinesis. We find that the divisome consists of two dynamically distinct subcomplexes: stationary ZBPs that transiently bind to treadmilling FtsZ fi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Consistent with this possibility, we observed that the average dwell time and percentage of the stationary FtsW-RFP population increased as the treadmilling speed of FtsZ decreased in GTPase mutant strains (Fig. 2f, Supplementary Table 4), in line with the observed increase in the dwell time of FtsZ monomers and FtsZ filament length in FtsZ GTPase mutants in a recent study (20). Interestingly, the average dwell time of stationary FtsW-RFP in wt cells (19.2±1.1s, Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with this possibility, we observed that the average dwell time and percentage of the stationary FtsW-RFP population increased as the treadmilling speed of FtsZ decreased in GTPase mutant strains (Fig. 2f, Supplementary Table 4), in line with the observed increase in the dwell time of FtsZ monomers and FtsZ filament length in FtsZ GTPase mutants in a recent study (20). Interestingly, the average dwell time of stationary FtsW-RFP in wt cells (19.2±1.1s, Fig.…”
Section: Resultssupporting
confidence: 89%
“…The average dwell time of stationary FtsW-RFP molecules, however, continued to decrease to ~10s (Fig. 4e, blue squares), approaching the mean lifetime of FtsZ monomers in the Z-ring (8.1 sec)(20).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Note that we do not model explicitly the stochastic on-reactions and off-reactions of individual subunits of an FtsZ filament, because such stochasticity is reflected in the treadmilling speed distribution of the filaments. The FtsZ filament length is set at 50 monomers (250 nm) and the treadmilling speed is independent of the filament length, in accordance to previous biochemical studies and a recent in vivo study 20,[32][33][34][35] . To discern principal interactions, the model considers one FtsI molecule and one FtsZ filament in a selfcontained septal section.…”
Section: Resultsmentioning
confidence: 84%
“…This process depends on FtsZ treadmilling and the activity of FtsZ-binding proteins, such as SepF, FtsA, ZapA or GpsB, which support filament formation, bundling, stabilization or membrane-anchoring (Eswara et al, 2018; Monteiro et al, 2018; Silber et al, 2020; Squyres et al, 2020; Whitley et al, 2020; Woldemeskel et al, 2017). Interestingly, our in vitro studies suggest that the SepH homologs from S. venezuelae and M. smegmatis display biochemical properties that are partially similar to the activities described for ZapA and GspB (Caldas et al, 2019; Eswara et al, 2018; Squyres et al, 2020; Woldemeskel et al, 2017). For example, similar to the effect described for GpsB, we found that SepH and SepH Ms stimulate FtsZ assembly (Eswara et al, 2018).…”
Section: Discussionmentioning
confidence: 99%